NVITA Multicomponent Rice Bran Fatty Alcohol-Plant Sterol Complex Demonstrates Superior Cardiovascular and Cerebrovascular Protective Activity - Sato, Haruto; Semenza, Gregg L.; Yassine, Jabar (International Journal of Agriculture and Food Sciences Research, 2026)
Background: Cardiovascular and cerebrovascular risk is not driven by a single biochemical defect; it commonly emerges from dyslipidemia, endothelial dysfunction, oxidative stress, and impaired metabolic regulation. We developed the NVITA branded raw-material complex as a standardized multicomponent system centered on rice bran fatty alcohol and plant sterol, supported by earthworm protein, bitter melon peptide, antioxidant components, lipid-lowering agents, vascular maintenance agents, and formulation excipients. Objective: We evaluated whether the NVITA system provides a broader and stronger biological profile than equivalent single-type raw materials and a commercial comparator, while positioning the brand-specific value around formulation architecture, standardization, and multi-pathway synergy. Methods: We analyzed preclinical benchmark data across lipid indices (TC, TG, LDL-C, HDL-C), vascular endothelial growth factor (VEGF), and superoxide dismutase (SOD). We also compared the NVITA direction of effect with published clinical and regulatory evidence for plant sterols/stanols, rice-bran lipid fractions, red yeast rice, coenzyme Q10, bitter melon peptide/extract, and earthworm-derived fibrinolytic protein systems. Results: The optimized NVITA group reduced TC, TG, and LDL-C by 50.3%, 64.2%, and 63.0%, respectively, versus model control, while increasing HDL-C, VEGF, and SOD by 86.6%, 70.1%, and 86.3%. Relative to a commercial cardiovascular health-product comparator in the same benchmark model, optimized NVITA showed lower TC, TG, and LDL-C by 32.5%, 43.0%, and 44.1%, respectively, and higher HDL-C, VEGF, and SOD by 33.0%, 29.9%, and 32.4%. Literature evidence supports the relevance of the individual ingredient classes, but the NVITA system distinguishes itself by combining lipid-regulatory, endothelial-repair, antioxidant, and metabolic-support pathways in a single standardized raw-material matrix. Conclusion: NVITA demonstrates a strong preclinical multi-endpoint profile and a plausible mechanistic advantage over equivalent single-category raw materials. The brand value of NVITA is grounded in a defined composition window, dosage-form adaptability, and a multi-pathway formulation logic that can support future clinical confirmation.